The Effect of Air Pollution on Body Weight and Obesity: Evidence from China - Olivier Deschenes; Huixia Wang; Si Wang; Peng Zhang (Institute of Labor Economics (IZA), 2019)
We provide the first study estimating the causal effect of air pollution on body weight. Using the China Health and Nutrition Survey, which provides detailed longitudinal health and socioeconomic information for 13,226 adult individuals over 1989-2011, we find significant positive effects of air pollution, instrumented by thermal inversions, on body mass index (BMI). Specifically, a 1 Îg/m3 (1.59%) increase in average PM2.5 concentrations in the past 12 months increases BMI by 0.31%, and further increases the overweight and obesity rates by 0.89 and 0.19 percentage points, respectively. Our paper identifies a new cause of obesity, and sheds new light on the morbidity cost of air pollution.
Keywords: I12; I15; Q53; 330; air pollution; obesity; weight gain; China